Exploring Teachers’ Satisfaction and Students’ Entrepreneurial Competencies in Four Entrepreneurial Programs Carried Out in Extremadura (Spain) Schools - Maldonado Briegas, Juan José; Citarella, Antonio; Sánchez Iglesias, Ana Isabel; Gonzáles Ballester, Sergio; Alvarez Marínez, A. Javier; Vicente Castro, Florencio (Frontiers in Psychology, 2021)
The question of whether the entrepreneur is born or made, forces us to respond that the entrepreneurial culture clearly breaks with the myth that entrepreneurs are born. Currently, it is considered that entrepreneurial skills can be acquired like any other discipline and that is why it should be taught (Timmons, 2003). Their teaching and learning are key to the well-being of the teacher and to the positive achievement of the students. The entrepreneurial culture is an educational objective of developed societies and has its origin in the business culture (Peña-Calvo et al., 2015). There are two current models, American and European (Erkkilä, 2000). The one that develops in the Extremadura region (Spain), based on the European model, tries to create a vital state in the participating students that enhances competences such as creativity, personal initiative or self-confidence, elements that try to generate a true motivation to undertake. The motivated, accomplished and positive teacher contributes to that achievement and achieving it favors the well-being of teachers. It's a round trip. It is a "do ut des". In our research, we evaluated four entrepreneurial culture programs in the classroom: "Junioremprende", "Teenemprende", "Experemprende", "Youthemprende". The teachers involved in the programs are 356, and the valid questionnaires are 154. The students enrolled in the programs are 4800, and the questionnaires valid 1198. The results of our research, according to a seven-point Likert scale, gives a very high degree of teachers’ satisfaction.  The degree of teacher satisfaction for each of the programs and significantly means differences were found with Junior program resulted the more satisfied for teachers. For students, participation in the programs resulted in high development of entrepreneurial competencies. Similarly to teachers results, Junior program was found more significant in developing students’ entrepreneurial competencies indicating that entrepreneurial education is very appropriate for children. Findings of this study suggest that entrepreneurial education should be encouraged for students at every stage of education.